Survey of Fasciola hepatica and other gastrointestinal parasitosis in dual-purpose cattle of the Sabana de Torres municipality, Santander, Colombia - Pinilla, Juan Carlos (2019)
The aim of this research was to determine the prevalence of Fasciola hepatica and other gastrointestinal parasites in dual-purpose cattle from the municipality Sabana de Torres, department of Santander, Colombia. Faecal and blood samples (n=196) were collected in 18 dual-purpose farms. The animals were stratified into three age groups: 0-12, 12-24 and >24 months. Faecal samples were processed by the McMaster and Dennis coprological techniques, and the presence of antibodies anti-F. hepatica was determined by an indirect ELISA test. The genera of the parasites were identified according to the size and morphology of their eggs or infective larvae. The overall prevalence of gastrointestinal parasites was 36.7%, with the highest values ​​for Eimeria sp (19.4%) and Paramphistomum sp (9.2%). The coprological and serological prevalence of F. hepatica was 4.1 and 6.1%, respectively, which reflects that the municipality Sabana de Torres is a hypoendemic zone for F. hepatica. A statistical association (p<0.05) was found between Eimeria sp parasitism and the age group.